CYTO-HISTOPATHOLOGICAL CORRELATION OF PREMALIGNANT AND MALIGNANT LESIONS OF THE ORAL CAVITY IN A TERTIARY CARE HOSPITAL - MEHER, GHANASHYAM; HEMBRAM, PABITRA; TUDU, KSHETRA MOHAN; SAHU, BINOD KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Globally, oral cancer seems to be the sixth-utmost common cancer. Oral cancer is the chief among entire malignant tumors of men in the Indian subcontinent and squamous cell carcinoma is the commonest among all oral malignancies. Hence, in the present study, the utility of aspiration and scrape cytology in the screening and initial diagnosis of oral lesions, to confirm by histopathology, were studied. Methods: The enrolled patients underwent complete clinical history, examination, fine-needle aspiration cytology (FNAC), scrape cytological assessment, and histopathological observations at VIMSAR, Odisha. Cytological smears were stained with Diff-Quik and Papanicolaou stains. Cytological observations were interrelated with concluding histopathological identification. Results: There were 32 premalignant and 60 malignant lesions of the oral cavity. Overall 69.56% diagnostic accuracy of scrape cytology for numerous intraoral premalignant and malignant lesions was found. The most common site for premalignant lesions was in the buccal mucosa, and malignancy was the tongue. Among the malignant lesion, squamous cell carcinoma was major, constituting 86.66% of cases, and most of the patients were in the fifth decade. Risk factor, mostly tobacco exposure, was associated with 66.66% of cases of a malignant lesion. Conclusion: FNAC and scrape cytology were observed as precise convenient, simple, and economical in the initial diagnosis of pre-cancerous and cancerous lesions of the oral cavity.